Genetic diversity and selection signatures in related Mediterranean breeds: Sarda, Pag, and Istrian sheep - Laura Falchi; Christina Marie Rochus; Marija Špehar; Jelena Ramljak; Ante Kasap; Nicolò Pietro Paolo Macciotta; Ivan Pocrnic; Alberto Cesarani (Small Ruminant Research, 2025)

Genome-based analysis for the identification of candidate genes associated with skin-photosensitization tolerance in sheep - Slim Ben Jemaa; Alberto Cesarani; Elena Ciani; Salvatore Mastrangelo (The Veterinary Journal, 2025)

Using tri-axial accelerometers data to predict behavior activity of grazing donkeys - Michele Congiu; Alberto Cesarani; Nicolò Pietro Paolo Macciotta; Salvatore Pier Giacomo Rassu; Valeria Giovanetti; Corrado Dimauro (Computers and Electronics in Agriculture, 2024)

Longitudinal Study on Seasonal Variation of Marine Biotoxins and Related Harmful Algae in Bivalve Mollusks Bred in Sardinia (Italy, W Mediterranean Sea) from 2015 to 2020 and Assessment of Potential Public Health Risks - Alessandro G. Mudadu; Anna Maria Bazzoni; Virgilio Congiu; Giuseppe Esposito; Alberto Cesarani; Rita Melillo; Giuseppa Lorenzoni; Simona Cau; Barbara Soro; Bruna Vodret; Domenico Meloni; Sebastiano Virgilio (Journal of Marine Science and Engineering, 2021)
Annual and interannual dynamics of shellfish toxins and associated harmful algal species (HAS) were analyzed from 2015 to 2020 in Tortolì Lagoon (Sardinia, west Mediterranean Sea). Analysis of seasonal occurrence of different harmful algae, such as Dinophysis spp., Prorocentrum spp., Pseudo-nitzschia spp. and Alexandrium minutum, was performed. The species Dinophysis acuminata and Dinophysis sacculus were responsible for the accumulation of lipophilic toxins belonging to the okadaic acid group (OAs) and pectenotoxins2 (PTX2) in bivalve mollusks. The highest HAS detection was recorded in the winter months; in particular, Dinophysis spp. was mostly present in January–February. Out of 1090 analyzed mollusk samples, 39 were non-compliant, exceeding the legal limits (160 μg OA eq/kg e.p.) reported in Regulation 853/2004 of the European Commission. A statistical analysis related to the presence of OA and PTX2 in mollusks with various environmental parameters (pH, water temperature, dissolved oxygen, algal density) was implemented, proving a clear winter seasonality. The present study highlights the necessity to better understand the different factors able to influence the production and accumulation of toxins in bivalve mollusks bred in an important Sardinian production area. The contribution of this research is important not only from an environmental and productive point of view but also from the view of implementing management in order to mitigate any harm to human health.